Resilience to climate change: community-based adaptation in Kenya and Senegal - Corner-Dolloff, Caitlin (2012)
Climate change is already having an impact on social, environmental and economic systems worldwide and will continue to pose significant challenges for human development over the decades to come. Communities that rely on natural resources for their livelihoods, especially in developing countries, are among those hardest hit. The international community is investing in planning and action to help countries adapt to climate change. The urgent question is how to channel funds towards the most vulnerable families and communities and how to prioritise adaptation initiatives that increase resilience most effectively.